Pengaruh Country Of Origin dan Promosi Pada Keputusan Pembelian Produk Smartphone: (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis, Universitas Nusa Nipa, TA. 2023/2024) - Yosefina Fitriani Londa; Antonius P. Kurniawan; Magdalena S. Samosir (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2024)
The research aimed to (1) examine the overview of Country of Origin, Promotion, and Purchase Decisions for smartphones among students of the Faculty of Economics and Business, Nusa Nipa University, Academic Year 2023/2024; and (2) analyze the influence of Country of Origin and Promotion on Purchase Decisions both partially and simultaneously. The population for this study consisted of 1,549 students from the Faculty of Economics and Business, Nusa Nipa University, Academic Year 2023/2024. The sample size was determined using Slovin’s formula, resulting in 100 individuals. Data were collected through an online questionnaire and analyzed using descriptive and inferential statistical methods, specifically multiple linear regression. Hypothesis testing was conducted using F-tests and t-tests. Descriptive analysis results indicated that the Country of Origin variable was categorized as good, Promotion was categorized as poor, and Purchase Decisions were categorized as fairly good. The t-test results showed that, partially, both Country of Origin and Promotion had a positive and significant effect on Purchase Decisions. The F-test results indicated that, simultaneously, all independent variables had a significant effect on Purchase Decisions. The coefficient of determination analysis showed that the two independent variables in this study could explain 16.9% of the variation in smartphone purchase decisions among students of the Faculty of Economics and Business, Nusa Nipa University, Academic Year 2023/2024.